Insights From a User Experience‐Focused Virtual Study on the Feasibility and Challenges of Decentralized Clinical Trials - Yue Ma; Le Li; Gaili Gao; Huan Zhou; Jianmiao Yang; Jiao Zheng; Li Zheng; Lu Zhang; Min Jiang; Pu Li; Wenjing Zhou; Xia Chen; et al. (Clinical and Translational Science)
ABSTRACT The decentralized clinical trial (DCT) approach may potentially improve patient accrual and diversity and reduce logistical burden; however, its implementation in China is still in its infancy due to limited practical experience and guidance. We utilized stakeholder engagement research to simulate DCT processes and investigate their feasibility and applicability in a local context. This study, conducted between October 2023 and June 2024, engaged stakeholders to simulate the roles of the investigator, study nurse/pharmacist, and patient in a DCT, and explored feasibility, challenges, and procedures locally. Using a mixed‐method approach including focus group interviews, heuristic evaluation, usability testing, surveys, and one‐on‐one interviews, four DCT elements (eConsent, direct‐from‐patient sample collection, televisits, and direct‐to‐patient investigational medicine delivery) were simulated at 11 Chinese investigational sites with 36 researchers. Pain points, stakeholder requirements, and key challenges were identified; standardized procedures and a user journey map were developed to provide a visual representation of the DCT process, encouraging broader adoption. The researchers reported high satisfaction across all DCT elements. Key challenges included patients' DCT system process ease of use, lack of thoroughness or attention remotely, integrating online (system) and offline (hospital/home) visits, patient risk management, maintaining medication compliance remotely, and DCT system compatibility, among others. Standard procedures were developed for each DCT element, addressing issues like identity verification and data privacy based on user perspectives. This study provided insights on implementing DCTs in China, identifying areas that need optimization to meet local regulatory and stakeholders' requirements. The standardized framework may be referenced when adapting future DCT elements.